2018
DOI: 10.1111/sltb.12449
|View full text |Cite
|
Sign up to set email alerts
|

Suicide Among Health Care Practitioners and Technicians in Colorado: An Epidemiological Study

Abstract: Suicide is a public health concern with risks that vary between occupation groups. Many suicide victims with a health care occupation die by poisoning, but few studies have epidemiologically studied this association. The objective of this study was to quantify the increased risk of suicide death by poisoning among health care professionals in Colorado. Eleven years (2004-2014, N = 8,753) of suicide deaths in Colorado were compiled from the Colorado Violent Death Reporting System. A retrospective cohort study u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…18 Risk of suicide is already high in healthcare professionals owing to easy means of access to drugs. 19 This will place these students in a highly vulnerable group and warrants prompt action by the Government and health care policymakers.…”
Section: Discussionmentioning
confidence: 99%
“…18 Risk of suicide is already high in healthcare professionals owing to easy means of access to drugs. 19 This will place these students in a highly vulnerable group and warrants prompt action by the Government and health care policymakers.…”
Section: Discussionmentioning
confidence: 99%
“…Skilled manual and lower-skilled occupations, such as construction workers, [5][6][7][8] cleaners, 7,9 labourers, 10 miners, 11 transport workers 12 and farmers 4,7 are overrepresented in suicide statistics. By contrast, non-manual and higher skilled occupations, excluding health professionals, 13,14 veterinarians 15 and emergency service workers, 16 are typically underrepresented. These findings are supported by a meta-analysis of 34 studies that indicated a stepwise gradient of risk, where the lowest skilled occupations were at the greatest risk of suicide compared with the highest skill occupations.…”
Section: Introductionmentioning
confidence: 99%